PENGARUH TINGKAT INFLASI DAN DANA PIHAK KETIGA TERHADAP PEMBIAYAAN DAN IMPLIKASINYA TERHADAP PENDAPATAN PADA BANK UMUM SYARIAH DI INDONESIA (Studi Kasus Bank Syariah Bukopin) - Leli Putri Ansari (JURNAL EKOMBIS, 2018)
The purpose of this research are to know the influence of inflation rate and third party funds to income on islamic ganeral bank in indonesia. The research using financial report islamic general bank bukopin period 2009-2015. The method analysis of the data used in this research is jalur analysis. The result showned that there is no influence between inflation rate and to financing. But third party funds is a positive and direct influence to financing. When is no influence between inflation rate and to bank earning but third party funds is direct influence to bank earning and financing is direct influence to bank earnings.Keywords: Bank earnings, financing, inflation rate, third party funds.